63.7k views
2 votes
Evaluate the expression (- n) ^ (n + n) + n ^ (n - n) , when n = 2

User Ian Auty
by
4.6k points

2 Answers

5 votes

Answer:

17

Explanation:

User Zpydee
by
5.6k points
4 votes

Answer:

17

Explanation:

Substitute the value of the variable and simplify.


(-(2))^((2+2)) +2^((2-2))


-2x^(2+2) =2^(4) = 16


2^(2-2) =2^(0)

Anything raised to the power of 0 is one.

16 + 1 = 17

User PavanKumar GVVS
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.